The neurogenic basic helix–loop–helix transcription factor NeuroD6 confers tolerance to oxidative stress by triggering an antioxidant response and sustaining the mitochondrial biomass - Uittenbogaard, Martine (American Society for Neurochemistry, 2010)
Preserving mitochondrial mass, bioenergetic functions and ROS (reactive oxygen species) homoeostasis is key to neuronal differentiation and survival, as mitochondria produce most of the energy in the form of ATP to execute and maintain these cellular processes. In view of our previous studies showing that NeuroD6 promotes neuronal differentiation and survival on trophic factor withdrawal, combined with its ability to stimulate the mitochondrial biomass and to trigger comprehensive antiapoptotic and molecular chaperone responses, we investigated whether NeuroD6 could concomitantly modulate the mitochondrial biomass and ROS homoeostasis on oxidative stress mediated by serum deprivation. In the present study, we report a novel role of NeuroD6 as a regulator of ROS homoeostasis, resulting in enhanced tolerance to oxidative stress. Using a combination of flow cytometry, confocal fluorescence microscopy and mitochondrial fractionation, we found that NeuroD6 sustains mitochondrial mass, intracellular ATP levels and expression of specific subunits of respiratory complexes upon oxidative stress triggered by withdrawal of trophic factors. NeuroD6 also maintains the expression of nuclear-encoded transcription factors, known to regulate mitochondrial biogenesis, such as PGC-1α (peroxisome-proliferator-activated receptor γ co-activator-1α), Tfam (transcription factor A, mitochondrial) and NRF-1 (nuclear respiratory factor-1). Finally, NeuroD6 triggers a comprehensive antioxidant response to endow PC12-ND6 cells with intracellular ROS scavenging capacity. The NeuroD6 effect is not limited to the classic induction of the ROS-scavenging enzymes, such as SOD2 (superoxide dismutase 2), GPx1 (glutathione peroxidase 1) and PRDX5 (peroxiredoxin 5), but also to the recently identified powerful ROS suppressors PGC-1α, PINK1 (phosphatase and tensin homologue-induced kinase 1) and SIRT1. Thus our collective results support the concept that the NeuroD6–PGC-1α–SIRT1 neuroprotective axis may be critical in co-ordinating the mitochondrial biomass with the antioxidant reserve to confer tolerance to oxidative stress.